1916. Diagnostic Stewardship in Infectious Diseases Molecular Viral Testing: A Pilot Project. (26th November 2018) - Corsi, Gabriela; Wanger, Audrey; James, Karen; Banner, Brian; Patel, Bela; Katz, Jeffrey; Ostrosky-Zeichner, Luis
Abstract: Background: Diagnostic tests are a crucial part of clinical care. However, they can often result in unnecessary testing with no patient impact. Diagnostic stewardship seeks to modify the process of ordering, performing and reporting diagnostic tests to improve resource utilization and patient outcomes. We have identified infectious diseases viral molecular tests that are meant for outpatient management that are often ordered during a hospital stay. Our objective was to quantify how often these tests were ordered and acted upon, as well as the cost associated with them. Methods: HIV quantitative PCR, HIV genotype and HCV genotype were selected as the target tests to be evaluated in this study. We measured the number of times these tests performed at Memorial Hermann Hospital TMC from January to December 2017. The individual and total cost of these tests were calculated. We sampled charts to determine whether the test had been acted on during or after the hospitalization. Results: During the study period, a total of 512 HIV viral loads, 29 HIV genotypes, and 58 Hepatitis C genotypes were ordered. The total expense on the HIV viral load tests was $43, 228, total expense on HIV genotypes was $8, 669, and for Hepatitis C genotype was $43, 055. Our chart sampling showed that HIV viral load was not acted on 65% of the time, HIV genotype test was not acted on 62% of the time and HCV genotype was not acted on 50% of the time. Conclusion: Three molecular viral tests that were acted upon less than 50% of the time they were ordered, collectively added an expense of $94, 952 over the course of a year at MHH TMC. A diagnostic stewardship program based on education and selective restriction of diagnostic testing may result in avoidance of unnecessary testing and substantial savings. Disclosures: All authors: No reported disclosures.